Rheological behavior of grout in context of Newtonian and non-Newtonian fund. - Kazemian, Sina; Prasad, Arun; Kim Huat, Bujang (Electronic Journal of Geotechnical Engineering, 2010)

(untitled)
The objective of this review is to elucidate the rheological behavior of cement based grout. Rheology of grouts is a way describing its properties without paying any intention to whether it is a homogeneous grout or a mixture of grains in grouts.